2019
DOI: 10.35940/ijrte.b1019.0782s719
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dried Noodles From Local Durian (Durio zibethinus L.) Seed Flour

Abstract: Durian seed flour contains nutritional chemical compound for consumption, especially carbohydrate and minerals that can be used as a substitution of wheat flour in various food products. Food diversification was conducted by utilizing natural resources through various steps such as processing durian seed flour as wheat flour replacement that fulfills the requirements of SNI (Standard Nasional Indonesia/ Indonesia National Standard) of wheat flour. The aim of this study was to utilize durian seed flour as a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…As the cut durian seed tissues exposed to oxygen in the air, polyphenol oxidase (PPO) enzymes inside the seeds oxidized the phenolic compounds quickly and naturally to o-quinones, thus contributed to the brown colour our and gum. Other ndings revealed that the presence of impurities such as natural pigments, tannin, endosperm, yellow germ from the durian seed, as well as the unpeeled slimy seed coat can also bring about the brownish colour in the extracted our and gum [7,20].…”
Section: Colourmentioning
confidence: 99%
“…As the cut durian seed tissues exposed to oxygen in the air, polyphenol oxidase (PPO) enzymes inside the seeds oxidized the phenolic compounds quickly and naturally to o-quinones, thus contributed to the brown colour our and gum. Other ndings revealed that the presence of impurities such as natural pigments, tannin, endosperm, yellow germ from the durian seed, as well as the unpeeled slimy seed coat can also bring about the brownish colour in the extracted our and gum [7,20].…”
Section: Colourmentioning
confidence: 99%